A case study of the effects of hybrid extensive reading on JFL learners' reading rates and comprehension. (July 2022) - Peterson, Jeff
Abstract: Research into the effects of extensive reading (ER) has surged over the past few decades. However, these studies almost exclusively focus on English language learners and tend to be limited by their lack of control over how the ER treatment is conducted. Furthermore, experimental and quantitative studies that investigate the possible effects of ER on the reading skills of learners of Japanese have yet to be fully explored. The goal of this study was to investigate the possible effects of hybrid ER on the reading rate development of learners of Japanese as a foreign language. This study also aimed to examine the level of comprehension learners maintained as their reading rates increased. Using a quantitative single-case study method, eight intermediate-level learners of Japanese were monitored while they engaged in hybrid ER and strictly adhered to ER principles over 2.5–4 months. Reading rate data, reading comprehension data, and general ER data were collected. Results showed that participants' reading rates increased significantly following the hybrid ER treatment and that comprehension abilities were not hampered by an increase in reading rate. This study provides evidence that hybrid ER has the potential to provide a highly enjoyable activity while substantially increasing learner reading rates without hindering comprehension.